2013
DOI: 10.1016/j.neuropsychologia.2012.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Non-linguistic learning and aphasia: Evidence from a paired associate and feedback-based task

Abstract: Though aphasia is primarily characterized by impairments in the comprehension and/or expression of language, research has shown that patients with aphasia also show deficits in cognitive-linguistic domains such as attention, executive function, concept knowledge and memory (Helm-Estabrooks, 2002 for review). Research in aphasia suggests that cognitive impairments can impact the online construction of language, new verbal learning, and transactional success (Freedman & Martin, 2001; Hula & McNeil, 2008; Ramsber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…However, persons with aphasia (PWA) have consistently been found to exhibit impaired performance not only on language measures, but also on measures assessing a variety of cognitive skills, including attention (Robin & Rizzo, 1989;Tseng, McNeil, & Milenkovic, 1993;Murray, Holland, & Beeson, 1998;Murray, 2000;Hunting-Pompon, Kendall, & Moore, 2011;Murray, 2012), memory (De Renzi & Nichelli, 1975;Albert, 1976;Gainotti, Silveri, Villa, & Caltagirone, 1983;Rönnberg, Larsson, Fogelsjöö, Nilsson, Lindberg, & Ängquist, 1996;Yasuda, Nakamura, & Beckman, 2000), executive function (Glosser & Goodglass, 1990;Beeson, Bayles, Rubens, & Kaszniak, 1993;Purdy, 2002), and learning (Vallila-Rohter & Kiran, 2013). Such findings suggest that the traditional characterization of aphasia as an impairment in language processing may be incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…However, persons with aphasia (PWA) have consistently been found to exhibit impaired performance not only on language measures, but also on measures assessing a variety of cognitive skills, including attention (Robin & Rizzo, 1989;Tseng, McNeil, & Milenkovic, 1993;Murray, Holland, & Beeson, 1998;Murray, 2000;Hunting-Pompon, Kendall, & Moore, 2011;Murray, 2012), memory (De Renzi & Nichelli, 1975;Albert, 1976;Gainotti, Silveri, Villa, & Caltagirone, 1983;Rönnberg, Larsson, Fogelsjöö, Nilsson, Lindberg, & Ängquist, 1996;Yasuda, Nakamura, & Beckman, 2000), executive function (Glosser & Goodglass, 1990;Beeson, Bayles, Rubens, & Kaszniak, 1993;Purdy, 2002), and learning (Vallila-Rohter & Kiran, 2013). Such findings suggest that the traditional characterization of aphasia as an impairment in language processing may be incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a small number of studies have explored learning in aphasia. These studies show that (a) learning ability is highly variable-but not universally impaired and (b) spared learning ability is associated with success in therapy Gupta et al, 2006;Vallila-Rohter & Kiran, 2013). The cognitive-linguistic factors that support successful learning ability and recovery in aphasia remain undetermined.…”
Section: Exploring Impaired Vs Spared Learning Performance In Aphasimentioning
confidence: 99%
“…A number of studies have explicitly evaluated verbal and non-verbal learning ability in adults with chronic aphasia (Gupta, Martin, Abbs, Schwart, & Lipinski, 2006;Kelly & Armstrong, 2009;Tuomiranta et al, 2011;Tuomiranta, Rautakoski, Rinne, Martin, & Laine, 2012;Vallila-Rohter & Kiran, 2013a, 2013b) and a detailed review of this research is provided in Chapter Five. This research has demonstrated that whilst individuals with aphasia are able to learn new information, both verbal and non-verbal learning mechanisms are impaired in adults with aphasia (Gupta et al, 2006;Kelly & Armstrong, 2009;Vallila-Rohter & Kiran, 2013a). Furthermore, consistent with language function, learning ability is heterogeneous in the aphasia population (Kelly & Armstrong, 2009).…”
Section: Influence Of Learning Ability On Aphasia Treatment Successmentioning
confidence: 99%
“…Research conducted in healthy adults has demonstrated successful learning for verbal information, irrespective of the presence or absence of feedback (Breitenstein et al, 2004;Vallila-Rohter & Kiran, 2013a). However, additional studies suggest that both the nature and the timing of feedback may be integral (Pashler, Cepeda, Wixted, & Rohrer, 2005;Pashler, Rohrer, Cepeda, & Carpenter, 2007).…”
Section: Theory Of Learningmentioning
confidence: 99%
See 1 more Smart Citation